Exploring Nurses' Knowledge and Experiences Related to Trauma-Informed Care - Stokes, Yehudis (Université d'Ottawa / University of Ottawa, 2016)
Background: Recognition of the significance of psychological trauma and its impact on individuals, families, communities, and society at large has greatly expanded over the past 20 years, calling for the need to develop both trauma-sensitive and trauma–responsive services. Nurses, as direct care providers who work within a holistic perspective, are positioned to play an integral role in the advancement of ‘trauma-informed care’ within healthcare services. Objectives: The specific objectives of this thesis were: a) to describe the use of social media (Facebook and LinkedIn) in the recruitment of Registered Nurses for an online survey, and b) to explore and describe the understandings and experiences related to trauma and trauma-informed care among nurses that scored the highest on this scale. Method: This was a two-phase study design using mixed methods. Phase One consisted of an online quantitative self-report survey. Participants were recruited via social media with the aim of examining nurses’ attitudes related to trauma-informed care. Phase Two consisted of a qualitative study exploring nurses’ knowledge and experiences related to trauma-informed care. The studies were conducted using a sequential approach; that is, the target sample for Phase Two (qualitative study) was identified based on the results of the survey (Phase One). Findings: From the first phase of this research, I proposed that social media, and specifically Facebook and LinkedIn, offer suitable platforms for recruiting a diverse sample of Registered Nurses to complete an online survey. Associated advantages and challenges as well as specific differences between Facebook and LinkedIn as recruitment platforms should be considered when incorporating these strategies. Four main categories emerged from the second phase of the research: “(Not)Knowing Trauma-Informed Care”, “Conceptualizing Trauma and Trauma- Informed Care”, “Nursing Care in the Context of Trauma”, and “Dynamics of the Nurse-Patient Relationship in the Face of Trauma”. These findings highlight important considerations for trauma including, the complex dynamics of trauma that affect care, the importance of both knowing trauma as a concept, but also knowing how to act in response to trauma knowledge, the need to facilitate trauma-informed care beyond mental healthcare, and the parallels between nursing and trauma-informed care. Conclusion: This Master’s thesis has explored the use of a novel survey recruitment strategy as well as emphasized the need for nurses and organizations to incorporate trauma-informed principles in the services they provide, and in their cultures as a whole. This research reinforces that the discipline of nursing is aptly situated to apply tenets of trauma-informed care and that we must further the progression of trauma-informed care in practice, policy, education, and research.
Keywords: nursing; trauma; mixed-methods; TIC